Study of mineralogical variability of ferruginous quartzites of productive strata of the eastern wing of the Petrovsky synclinal fold with using diagram Mm-Mo - Стеценко, В’ячеслав Валерійович; Зайченко, Валерія Валеріївна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Relevance of the problem. Petrovsky deposit is promising area for the extraction of magnetite ores. Detailed research on this deposit was carried out in the 80 years of the last century, but with the deepening and expansion of the pit data from previous studies have lost their relevance. In 2016-2018 years, in the north-eastern part of the deposit, an in-mine exploration in the direction of the eastern wing of the Petrovsky synclinal fold was carried out.Analysis of previous research. Petrovsky deposit of ferruginous quartzites is located in the remote southwestern part of the area of the Right Bank magnetic anomalies. Two groups of rocks were defined in the geological structure of the deposit: the crystalline rocks of the Precambrian base and the loose Cenozoic deposits that were on the top of them. Rocks of the Precambrian Age are highly metamorphosed and dislocated ones of the crystalline base and are represented by Archean and Lower Proterozoic formations. Lower Proterozoic formations are represented by the Ingul-Ingulets series which is divided by the (bottom up): zelenorichenska, artemivska, radionivska suites. The Artemivska suite is productive in the territory under investigation.In the structural plan, the Petrovskiy deposit is a compressed synclinal fold, the western wing of which is taper out, and the eastern wing extends in the northern direction. In connection with this, the object of research was the eastern wing.Purpose and tasks of research. The main purpose of the study was identification of the mineralogical variability of ferruginous quartzites, the allocation of mineralogical varieties of ores according to their chemical composition and to determine the regularities of expanding of these varieties within the productive strata of the eastern wing. These tasks were resolved using chemical analysis of rocks data, calculation of magnetic module MM and oxidation module MO, and the construction of a diagram in the coordinates of magnetization-oxidation of iron (MM-MO).Presentation of the main material of the article. Within the eastern wing of the Petrovsky synclinal fold, the eight mineralogical varieties of the ore were identified: silicate quartzites with magnetite, silicate-magnetite quartzites, magnetite-silicate quartzites, magnetite quartzites with hematite, hematite-magnetite quartzites, magnetite-hematite quartzites, hematite quartzites with magnetite. In the boundaries of the work area of a regular change of varieties of ores from hematite quartzites with magnetite in the central parts to silicate quartzites with magnetite on the periphery was established. In the same direction the regularities of changing the content of Fetot., Femagn. and sulfur (S) were elaborated. However, the authigenic-mineralogical zonality of the productive strata of the eastern wing of the syncline structure of the deposit was disturbed as a result of the overprint of metasomatic processes caused by the formation of bodies of aegirine and rebekitic metasomatites on the basis of ferruginous quartzites was established.